Filsafat Moral Islam Dalam Pandangan Murtadha Muthahari Dan Relevansinya Terhadap Pembinaan Akhlak Anak DI LPKA Tanjung Pati - Delfani Jasman (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2023)
The purpose of this research is to analyze the concept of Murtadha Muthahari's Islamic Moral Philosophy and to analyze the thoughts of Murtadha Muthahari's Islamic Moral Philosophy on the moral development of the fostered children at LPKA Class II Tanjung Pati.In this study, the type of research used is qualitative research that combines library research and field research. The research approach used in the literature study is a philosophical approach. The approach for field studies is to use an empirical research approach. The researcher used descriptive qualitative research. The results of this study are, first, Murtadha Muthahari's concept of Islamic moral philosophy explains how the concept of Islamic moral philosophy is that the introduction of God is the most basic concept of moral action. Humanity and morals will have no meaning without being accompanied by the introduction of God. Thus moral awareness is synonymous with Divine consciousness, which is further included in the category of worship. Second, one of the related forms of thought in Islamic moral philosophy in the view of Murtadha Muthahari is that moral awareness is synonymous with Divine consciousness. by worshiping Allah and getting closer to Allah with the aim of forming an awareness of the moral actions of the fostered children to become even better deeds based on the teachings of the Qur'an and Sunnah. The need for awareness of moral actions, will determine how the manner or attitude of the fostered child in acting in accordance with the development of an increasingly advanced era. Keywords: Islamic Moral Philosophy, Murtadha Muthahari, Fostered Children